A simple and green strategy for preparing poly(vinyl alcohol)/phosphate cellulose aerogel with enhanced flame‐retardant properties. Issue 3 (9th December 2020) - Jixuan, Wei; Chunxia, Zhao; Yunchao, Li; Yuntao, Li; Zhangmei, Sun; Dong, Xiang; Hui, Li
Abstract: Phosphorylated celluloses (PCFs) were obtained via reaction of microcrystalline cellulose with phosphorous acid in molten urea. Fourier transform infrared spectroscopy and scanning electron microscopy were used to observe the chemical structure and microstate of the PCFs. A flame retardant glutaraldehyde cross‐linked poly (vinyl alcohol)/PCF aerogel was fabricated using a melt cross‐link and freeze‐dried method. The results of thermogravimetric analysis confirmed that the thermal stability of the poly(vinyl alcohol) (PVA) aerogels incorporating PCF is more outstanding. The peak of heat release rate (PHRR) and the total heat release (THR) values of the PCA/PCF10 aerogel deceased obviously by 33.8 and 64%, respectively, compared to the corresponding values for the pure PVA aerogel; these changes confirm that the PCA/PCF aerogel had better flame‐retardant properties than the pure PVA aerogel. Moreover, the fire performance index and fire growth index indicate that the introduction of PCF would diminish the occurrence of fire. Abstract : Poly(vinyl alcohol)/phosphate cellulose cross‐linked aerogels were designed and prepared for enhancing flame‐retardant properties. The cross‐linked structure favored better thermal performance and higher flame retardant performance compared to pure poly(vinyl alcohol) aerogel.